1980
DOI: 10.1149/1.2129392
|View full text |Cite
|
Sign up to set email alerts
|

Control of Zn Doping for Growth of InP pn Junction by Liquid Phase Epitaxy

Abstract: The method of Zn doping for the liquid phase epitax/al growth of a high quality InP pn junction has been investigated. The evaporation of Zn from the growth melt was found appreciable at the growth temperature as low as 640~ and therefore causing the unwanted Zn diffusion into the substrate from the vapor. The diffusion of Zn from the growth melt was also observed and its effective diffusion coefficient in undoped InP was estimated to be 1.0 _.+ 0.3 X 10 -1~ cm 2 sec -I at. 620~176The characterization of grown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1981
1981
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…InGaAsP (λ g =1.3µm, d=50nm) and InGaAsP (λ g =1.1µm, d=100nm) are nominally nondoped posses high leakage current. This effect can be caused by the following factors: -the structure defects, especially dislocation network threading through multiheterostructure (PETROFF), -injected carriers may leak through the heterostructure bariers (WADA et al), or the active region is contaminated by zinc from InP:Zn confinement layer (WADA et al, 1980), On the basis of I-V characteristics measured we suggested a modification of prepared multiheterostructure by doping every second a thin layer of InGaAsP (λ g =1.1µm) inside the active region by cobalt. Semiinsulating properties conferred by cobalt impurity can suppress contamination by active impurities and improve the function of heterobarriers during the injection process.…”
Section: Measurements Methods and Resultsmentioning
confidence: 99%
“…InGaAsP (λ g =1.3µm, d=50nm) and InGaAsP (λ g =1.1µm, d=100nm) are nominally nondoped posses high leakage current. This effect can be caused by the following factors: -the structure defects, especially dislocation network threading through multiheterostructure (PETROFF), -injected carriers may leak through the heterostructure bariers (WADA et al), or the active region is contaminated by zinc from InP:Zn confinement layer (WADA et al, 1980), On the basis of I-V characteristics measured we suggested a modification of prepared multiheterostructure by doping every second a thin layer of InGaAsP (λ g =1.1µm) inside the active region by cobalt. Semiinsulating properties conferred by cobalt impurity can suppress contamination by active impurities and improve the function of heterobarriers during the injection process.…”
Section: Measurements Methods and Resultsmentioning
confidence: 99%
“…As-grown InGaAsP/InP avalanche photodiodes have also shown the lowest leakage current and excess noise factor (15). Zinc, cadmium, and magnesium have been used as p-type dopants for InGaAsP LPE layers (16)(17)(18)(19)(20)(21), but not without problems. Junction misplacement has commonly been observed for zinc-doped epilayers (18).…”
Section: Fig 9 Transmission Cathodoluminescence Of the Buffer Layer S...mentioning
confidence: 99%
“…Coleman (18) and Wada et a~. (19) capped their melts to reduce cross contamination and thus minimize one source of "anamolous" zinc diffusion. Wada et at.…”
Section: Fig 9 Transmission Cathodoluminescence Of the Buffer Layer S...mentioning
confidence: 99%
See 1 more Smart Citation
“…The most widely used p-type dopant for MOCVD InP is zinc [4,5]. Epitaxial layers of Zn-doped InP have also been grown using different deposition techniques, such as liquid phase epitaxy (LPE) [6], and both hydride [7] and chloride [8] chemical vapour deposition (CVD). Zinc-doped bulk crystals of InP have been grown by the liquid encapsulated Czochralski (LEC) method [9].…”
Section: Introductionmentioning
confidence: 99%